Reestablishment of an algae-bacteria pest model using continuous passage in the laboratory - Nguyen, Thuy M.; Abeykoon, W. K. N. L.; Corcoran, Alina A. (Frontiers in Microbiology, 2026)
IntroductionThe paucity of laboratory models comprising predatory bacteria infecting microalgae hinders our understanding of bacteria that predate or parasitize algae both in aquatic ecosystems as well as algal cultivation systems. In 2015, a novel predatory bacterium was found in open cultivation ponds of Nannochloropsis salina located in Las Cruces, New Mexico (NM). This bacterium, “FD111”, caused the crash of large-scale cultures in the field, and transfer of the infection source into healthy N. salina cultures in the lab killed them. However, research on this pest has been slow due to difficulties cultivating it under laboratory conditions.MethodsIn this study, we continuously passaged two infection sources of an FD111-like pest collected in the field in 2023 into two cultures of Nannochloropsis oceanica, CCAP849/10 and a field-adapted culture of the same isolate, with the purpose of enriching for the pest. We passaged the pest into healthy cultures ten times. At each passage, we collected data on the biomass and health of algae cultures and collected samples for 16S sequencing. We also documented the life cycle of the pest via transmission electron microscopy.ResultsContinued passaging of the infection source to healthy algal cultures was a reliable approach to maintain pest viability in the lab, although it did not help to enrich the pest concentration, likely due to the timing of each passage. Following each passage, infected cultures deteriorated and, after four days, died. Transmission electron microscopy showed that a pest similar to FD111 attached to N. oceanica cells, replicated inside the cells, and exited the cells after replication – leaving ghost cells. In this study, the FD111-like bacterium had a rod shape and single flagellum, whereas the originally described FD111 had two distinct phenotypes: a rod and hook shape. The 16S microbial community analysis indicated that the FD111-like bacterium falls within the Oligoflexales order, possibly the Pseudobacteriovorax genus. Sequencing also revealed that the pest was not dominant within the bacterial community, accounting for as little as 3% of the operational taxonomic units.DiscussionThis paper shows that continuous passage can be an alternative approach to isolation and cultivation of pests, and lays the groundwork for additional research and development on this and similar pests. The finding that cultures crashed with a putative pest of low abundance suggests that this pest could be a keystone species in aquatic ponds. Additional work is needed to determine the mechanisms of infection and inform crop protection strategies.